PENGARUH MEDIA GAMBAR TERHADAP KEMAMPUAN MENULIS PUISI SISWA - Sinta Maria Dewi (Jurnal Sekolah Dasar, 2018)
Abstract: This research aims to know the Influence of Media Image on the ability of Writing Poetry students. The method used in this study is a random method that does not use posttes control group design method. The findings of this study show the average way of writing poetry on students by using the image media (experimental class) higher average poetry writing skills on students who were taught with conventional learning (control class). The average of pretest experiments obtained by experiment class is 63,75. The average pretest class of control class is 61,05. After the second class action, the average posttest of the experimental class is 79.45 and the control class is 74.95. Hypothesis calculation using t paired t test test and significance of 0.05 significant level indicates probability (significance) is 0,033. Because of the significance of 0.033